Payments' Impact On Indian Agricultural Imports - Battula Vijay Kiran , A. Narasimha Rao (Migration Letters, 2022)
This study explores the correlation between overarching payment statistical metrics in India and the import patterns of approximately 40 key agricultural commodities governed by the Agricultural and Processed Food Products Export Development Authority (APEDA). Employing distinct regression analyses for import transactions exclusively, spanning the period from 2013-14 to 2021-22, our results reveal that only a subset of these commodities exhibits discernible effects from payment metrics. As digital payment methods gain prominence, the identification of [1]agricultural products unaffected by payment trends holds substantial implications for the financial sector. The recognition that certain agricultural products maintain independence from payment trends underscores the necessity for comprehensive interventions and further inquiry. Emphasizing the significance of thoroughly exploring these dynamics, this study offers insights to guide strategic decision-making and policy formulation aligned with the evolving financial landscape.